Investigations on structural, optical, morphological and electrical properties of nickel oxide nanoparticles. (2015) - Sagadevan, Suresh; Podder, Jiban
Nickel oxide (NiO) nanoparticles have been prepared by chemical co-precipitation method. The synthesised nanoparticles were investigated by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible spectroscopy and dielectric studies. The formation of NiO nanoparticles was confirmed by X-ray diffraction (XRD). The morphology and size of the NiO nanoparticles were characterised using scanning and transmission electron microscopy (SEM and TEM). The optical properties were studied by the UV-visible absorption spectrum. The dielectric properties of NiO nanoparticles were studied in the frequency range of 50 Hz5 MHz at different temperatures. Further, electronic properties, such as valence electron plasma energy, average energy gap or Penn gap, Fermi energy and electronic polarisability of the NiO nanoparticles were calculated. The AC conductivity of the NiO nanoparticles increases with increase in temperature and frequency. The activation energy was calculated from AC conductivity studies.